Teacher Development Model to Facilitate Science Teaching through the Concept of Professional Learning Community - Polyiem, Titiworada; Asawaniwed, Pongthorn (European Scientific Journal, ESJ, 2023)
This research aimed to develop and evaluate a teacher development model that enhances science learning management based on professional learning community principles. In the initial phase, input was obtained from five experts in science learning management. This model was further refined with insights from experts in curriculum design, assessment, and evaluation. The model’s impact was tested with 16 science teachers from eight schools under the Roi Et Municipality during the second semester of the academic year 2022. The research tools included the teacher development model, a quality assessment metric for science learning, and a teacher satisfaction survey. Data were analyzed using basic statistical methods, with the Wilcoxon Signed Rank Test for hypothesis validation. The results identified four key strategies: Learning Management Design, Learning Activity Organization, Use of Learning Media and Resources, and Learning Measurement and Evaluation. The model comprises six primary components: origin, objectives, principles, structure, content, and teaching process. The quality of science teaching improved over two phases, with a significant difference in quality scores at a 0.05 level. The model received positive feedback, with a satisfaction score averaging 4.52.